Blood Donation, Being Asian, and a History of Iron Deficiency Are Stronger Predictors of Iron Deficiency than Dietary Patterns in Premenopausal Women. (11th June 2014) - Beck, Kathryn L.; Conlon, Cathryn A.; Kruger, Rozanne; Heath, Anne-Louise M.; Matthys, Christophe; Coad, Jane; Jones, Beatrix; Stonehouse, Welma
Abstract : This study investigated dietary patterns and nondietary determinants of suboptimal iron status (serum ferritin < 20  μ g/L) in 375 premenopausal women. Using multiple logistic regression analysis, determinants were blood donation in the past year [OR: 6.00 (95% CI: 2.81, 12.82); P < 0.001 ], being Asian [OR: 4.84 (95% CI: 2.29, 10.20); P < 0.001 ], previous iron deficiency [OR: 2.19 (95% CI: 1.16, 4.13); P = 0.016 ], a "milk and yoghurt" dietary pattern [one SD higher score, OR: 1.44 (95% CI: 1.08, 1.93); P = 0.012 ], and longer duration of menstruation [days, OR: 1.38 (95% CI: 1.12, 1.68); P = 0.002 ]. A one SD change in the factor score above the mean for a "meat and vegetable" dietary pattern reduced the odds of suboptimal iron status by 79.0% [OR: 0.21 (95% CI: 0.08, 0.50); P = 0.001 ] in women with children. Blood donation, Asian ethnicity, and previous iron deficiency were the strongest predictors, substantially increasing the odds of suboptimal iron status. Following a "milk and yoghurt" dietary pattern and a longer duration of menstruation moderately increased the odds of suboptimal iron status, while a "meat and vegetable" dietary pattern reduced the odds of suboptimal iron status in women with children.